INTEGRATIVE MINISTERIAL TRAINING: METHODOLOGICAL AND PEDAGOGICAL INTEGRATION WITHIN THE CURRICULUM - M. Naidoo (Acta Theologica)
Within theological education, there are ongoing concerns that ministry education is dis-integrating and needs to recover by engaging a holistic focus. Training institutions are criticised for producing academically astute graduates, who lack the pastoral exposure or the required spirituality for Christian ministry. As ministry situations become more complex, an integrative approach to teaching and learning is required, since it connects learning to experience in an intentional way. Despite its complexity in implementing, integration as a method should be embraced more fully in the design and reformation of theological education. This article discusses proposals that can create spaces for integration, highlighting the place of disciplines of knowledge in curricular approaches, the theory-practice challenge, together with fostering active teaching and learning. These proposals are important considerations for purposeful theological education in this time of complex curricular changes in higher education.